IoT : home-based monitoring system - Lin, Shi Zheng (Nanyang Technological University, 2021)
Internet of Things has been experiencingexponential growth in the recent years. Every day, hundreds of devices are being connected to the internet, these devices can be controlled by the user via Mobile Applications or Web Browsers through any devices with an internet connection. These devices can range from day to day machines such as a coffee maker, to more sophisticated machines such as monitoring systems. While there are a wide variety of IoTdevices, one thing they have in common is that they have the potential to improve user convenience.This final year project aims to create a simple Home-based Monitoring system that is affordable and easy to build. The project will be built onthe NodeMCU ESP8266 Wi-Fi module, with various sensorsas well as cameras connected to the module. The system can then be controlled through a Mobile Application known as Blynk.